A study on heavy metal content in seaweeds from peninsular Malaysia - Tan Sin Lee (Universiti Putra Malaysia Terengganu, 2014)
Seaweed and seawater samples were collected from thirteen locations along the beaches of Peninsular Malaysia.A total of 8 species of Chlorophyta,6 species of Rhodophyta,4 species of Phaeophyta and 1 species of Cyanophyta were then analyzed for five metals namely Cu,Cd, Cr,Fe and Zn by atomic absorption spectrophotometry.The seawater samples were analyzed for Cu,Cd,Pb and Zn.